What Determines Muslim-Friendly Tourism in Aceh? - Musa, Armiadi; Halim, Hendra; Khalidin, Bismi; Ibrahim, Azharsyah (Ekonomi Syariah IAIN Kudus, 2021)
Aceh is the only province in Indonesia legally allowed to implement sharia law across all sectors, including the tourism industry. This study aims to analyze factors influencing Muslim-Friendly Tourism (MFT) in Aceh. Specifically, it examines the direct and indirect relationship between MFT with travel intention, destination image, and tourist attitude. Data is gathered through a questionnaire survey among 150 respondents that were selected using the convenience sampling method. To explain the tourist’s travel intentions, this study develops and tests a multiple regression analysis using the extended hierarchical linear modeling. Seven hypotheses were proposed regarding the relationships between MFT, tourist attitude, destination image, and travel intention constructs. The empirical results from the structural model suggest that MFT, destination image, and tourist attitude significantly influence travel intention; destination image and tourist attitude are the perfect mediators in influencing the MFT on travel intention to Aceh. These results have the implication in improving the promotions of tourism destinations in Aceh and developing more effective halal tourism positioning strategies for Aceh in particular and Indonesia in general.